Microplastics in Demersal Sharks From the Southeast Indian Coastal Region - Janardhanam, Madhuvandhi; Sivakumar, Priya; Srinivasan, Gomathi; Sivakumar, Rekha; Marcus, Priscilla Niranjani; Balasubramaniam, Sujatha; Rajamanickam, Krishnamurthy; Raman, Thiagarajan; Singaram, Gopalakrishnan; Harikrishnan, Thilagam (Frontiers in Marine Science, 2022)
Microplastic (MPs) contamination has emerged as a serious worldwide issue. Human activity, commercial enterprises, and fishing are concentrated around the seashore, causing high levels of MPs contamination in coastal and marine organisms. When it comes to their vulnerability to MPs ingestion, sharks are least studied organism. The objective of this study is to investigate MPs accumulation in sharks collected from the Southeast Indian coastal zone (Bay of Bengal). We present evidence of MPs ingestion in demersal sharks caught by the trawlers during trawling operations in marine waters beyond a depth of 80 m in the Southeast India coast. Shark samples were also checked for any gender or size differences in contaminant loading. Gill and gut (digestive tract) were examined in 40 sharks and 82.5% of samples contained at least one MP particle. The average number of MP particles was found to be 4.67 items per individual shark; the gastrointestinal tract showed more MPs than the gills. The majority of the MPs were blue and pale white followed by black and transparent particles with diameters ranging from 0.5 to 2 mm. The fibre fragments were prevalent in the intestines of the shark. Fourier Transform Infrared (FT-IR) spectroscopy revealed that the bulk of polymers were polypropylene (PP), polyacrylamides (PA), and polyethylene (PE). MPs contamination poses an unknown level of harm to shark species. The present study revealed the first scientific data of MPs and associated fibre ingestion in shark species in their habitat in the Bay of Bengal.